MATHEMATICAL ANALYSIS OF NON-GAUSSIAN REGIME ORIGINATION IN NUMERICAL INTEGRATION OF ISOELECTROFOCUSING PROBLEM - Lyudmila V. Sakharova (Advanced Engineering Research)
The mathematical analysis of the problem of so-called “non-Gaussian” regimes in the computational solution of the integro-differential isoelectric focusing (IEF) problem is done. Due to the problem analytic transformation, the development of the optimization algorithms and the numerical asymptotic testing, it is found that non-Gaussian regimes are the property of the original mathematical problem, and not the computational error accumulation consequence.